STRATEGI MENGATASI TERGANGGUNYA PENGOPERASIAN STEERING GEAR DI KAPAL SV. SWISSCO SAMSON - Tony Santiko (Politeknik Ilmu Pelayaran Semarang, 2019)
ABSTRACTThe aircraft streeing gear is one of the auxiliary machineries that functions forchange and determine the direction of motion of the ship, both straight and turn the ship, to the left (portside) and to the right (starboard side), by moving the rudder (steering wheel). MethodThe research used in this study is a quantitative method. Data analysis techniqueusing the Urgency, Seriousness, and Growth (USG) method by determining priority levelsIssues use a scale of numbers in order to get an effective and effective issue resolution withmaintain the performance of Steering Gear in SV. SWISSCO SAMSON then do maintenanceand repairs as desired. Based on the results of research that has been done by researchers,steering gear does not work optimally, caused by not operating the system value properly,there are several bolts or connections (connectors) to the pipe that loosens, the quality and type of oilimproper hydraulic applications, damage to seals and o-rings. Decreased pump performancehydraulics, caused by leakage of pipe joints, damage to valves, loss of qualityhydraulic oil, dirty or clogged filters and leaks in hydraulic cylinders. To overcomethese factors can be done by regularly checking the electric-hydraulicsteering gear, checking the pump, checking the pipe leading to the pumphydraulics, hydraulic pump valves, hydraulic oil quality checking